2013
DOI: 10.1104/pp.113.232637
|View full text |Cite
|
Sign up to set email alerts
|

A Nodule-Specific Lipid Transfer Protein AsE246 Participates in Transport of Plant-Synthesized Lipids to Symbiosome Membrane and Is Essential for Nodule Organogenesis in Chinese Milk Vetch      

Abstract: Rhizobia in legume root nodules fix nitrogen in symbiosomes, organelle-like structures in which a membrane from the host plant surrounds the symbiotic bacteria. However, the components that transport plant-synthesized lipids to the symbiosome membrane remain unknown. This study identified and functionally characterized the Chinese milk vetch (Astragalus sinicus) lipid transfer protein AsE246, which is specifically expressed in nodules. It was found that AsE246 can bind lipids in vitro. More importantly, AsE246… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 65 publications
4
70
0
Order By: Relevance
“…The expression pattern of nsLTPs from different plants has shown a large divergence covering various tissues and against environmental stimulates (George and Parida 2010;Kader 1996;Pitzschke et al 2013;Pyee et al 1994). Consistent with their complex expression profiles, the pleiotropic functions of nsLTPs have been previously suggested to be involved in cuticle synthesis (Lee et al 2009;Pyee et al 1994), catabolism in lipid storage (Tsuboi et al 1992), somatic embryogenesis (Kader 1996), stigmapollen interaction (Huang et al 2013;Mollet et al 2000;Tian et al 2013), defense signaling (Blein et al 2002;Maldonado et al 2002), nodule organogenesis (Lei et al 2014) development, and antimicrobial activities (Caaveiro et al 1997;Kristensen et al 2000). However, the exact function of nsLTPs remains to be clearly established.…”
Section: Introductionmentioning
confidence: 90%
“…The expression pattern of nsLTPs from different plants has shown a large divergence covering various tissues and against environmental stimulates (George and Parida 2010;Kader 1996;Pitzschke et al 2013;Pyee et al 1994). Consistent with their complex expression profiles, the pleiotropic functions of nsLTPs have been previously suggested to be involved in cuticle synthesis (Lee et al 2009;Pyee et al 1994), catabolism in lipid storage (Tsuboi et al 1992), somatic embryogenesis (Kader 1996), stigmapollen interaction (Huang et al 2013;Mollet et al 2000;Tian et al 2013), defense signaling (Blein et al 2002;Maldonado et al 2002), nodule organogenesis (Lei et al 2014) development, and antimicrobial activities (Caaveiro et al 1997;Kristensen et al 2000). However, the exact function of nsLTPs remains to be clearly established.…”
Section: Introductionmentioning
confidence: 90%
“…Previous studies suggested that lipid transfer proteins (LTPs) are likely the candidates delivering the phospholipids to developing cells61415 considering that most LTPs are abundantly expressed in the epidermis of developing tissues16171819. LTPs contain a hydrophobic pocket capable of binding long chain fatty acids1720, and studies showed that plant LTPs are involved in transporting lipids from the endoplasmic reticulum (ER) to plasma membrane (PM) and subsequently from PM to the cell exterior212223.…”
mentioning
confidence: 99%
“…Some are also involved in physiological processes such as pollenstigma interaction (Huang et al, 2013;Tian et al, 2013) and organogenesis of nodules (Lei et al, 2014). Working on systemic acquired resistance, Maldonado et al (2002) showed that LTPs can also be directly related to defense signaling.…”
Section: Discussionmentioning
confidence: 99%